Modeling and free vibration analysis of rotating hub-blade assemblies reinforced with graphene nanoplatelets. (November 2021) - Zhao, Tian Yu; Jiang, Ze Yu; Zhao, Zhan; Xie, Li Yang; Yuan, Hui Qun
This paper presents a new theoretical model for rotating elastic hub-blade assemblies, made of functionally graded (FG) graphene nanoplatelet (GPL) reinforced nanocomposites, and their free vibration characteristics are investigated. This model is the first attempt to include two elastic components simultaneously and consider the coupled effect. The Euler-Bernoulli beam theory and the Donnell's shell theory are employed to establish the mathematic model of the blade and hub, respectively. The effective material properties, varying continuously along the thickness of the beam and cylindrical shell, are determined via the Halpin-Tsai micromechanics model and the rule of the mixture. The Lagrange's equation is adopted to derive the equations of motion which are then solved by employing the substructure mode synthesis method and the Galerkin method. A parametric study is conducted to examine the effects of the rotating speed, graphene nanoplatelet distribution pattern, GPL weight fraction, length-to-thickness ratio and length-to-width ratio of graphene nanoplatelets (GPLs) and blade dimension on the natural frequencies of the nanocomposite rotor system, which will significantly benefit on the structural and material design of GPL reinforced hub-blade assembly.